Pentingnya Lingkungan dan Interaksi Sosial dalam Perkembangan Bahasa Anak Usia Dini - Umi Salamah; Syamsiah Depalina (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to examine the importance of environment and social interaction in supporting early childhood language development. The research was conducted on Jalan Perjuangan, Dalan Lidang Subdistrict, using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving children aged 4–6 years, teachers, and parents. The findings reveal that a linguistically rich environment and active, positive social interactions both at home and in educational settings have a significant impact on children's language skills. Children raised in supportive environments and frequently engaged in conversations, cooperative play, and storytelling activities show better vocabulary growth, sentence structure development, and communication abilities. In conclusion, environment and social interaction play a vital role in shaping early childhood language competence and should be given serious attention by parents, educators, and the surrounding community.